A política de gestão de pessoas da UFPA: em sintonia com o gerencialismo? - Tavares, Denise de Lourdes de Andrade (2010)
This research examined the personnel policies of the Federal University of Pará (UFPA), aimed at the middle area, implemented by the President's Office of Personnel Management (PROGEP), through the Performance Management and Development from 2006 to 2009 period, in which Institutional Plan was implemented for Technical and administrative (PIDT) with a view to ascertaining whether these actions were developed in line with the ideas of managerialism or New Public Management (NPM). The study opted for qualitative research using interview as a tool to collect data. The informants were managers PROGEP / UFPA who acted in that period. Data interpretation was based on analysis of content from the collation of speeches and documents produced during the period with the managerial categories. Data analysis revealed that the management of people, UFPA has the characteristics of a hybrid management, observing the period studied two models of management: a bureaucratic, rational, focused on processes, contemporary face of public organizations, and other managerialist, adopted by PROGEP in obedience to the mandatory policies of the federal government, being much more present the characteristics of a personnel policy-oriented processes. Concludes that the personnel policy of the UFPA has not been fully tuned to managerialism in the surveyed period